Investigation of Chloramines, Disinfection Byproducts, and Nitrification in Chloraminated Drinking Water Distribution Systems - Abulikemu, Gulizhaer (Journal of environmental engineering (New York, N.Y.), 2022)
Four chloraminated drinking water distribution systems (CDWDSs) required to maintain numeric versus "detectable" residuals were spatially and temporally sampled for water quality and associated trihalomethane (THM) and haloacetic acid (HAA) formation. Monochloramine decreased from entry point (EP) to maximum residence time (MRT) samples while THMs and HAAs initially increased and then stabilized or slightly decreased. Subsequently, EP and MRT samples were used in laboratory-held studies to further evaluate disinfectant residual stability, chloramine speciation, and nitrification occurrence. MRT water exhibited a faster monochloramine concentration decline compared to EP water, indicating a decreasing disinfectant residual stability from increasing water age through distribution. Using a simple technique based on published inorganic chloramine chemistry, samples were also investigated for nondisinfectant positive interference (NDPI) on total chlorine measurements. NDPI concentrations represented up to 100% of the total chlorine concentration when total chlorine concentrations decreased to 0.05 mg-Cl2/L, indicating little to no effective disinfectant residual remained